Influencia de las épocas de poda sobre el rendimiento de la Vid (vitis labrusca), variedad Borgoña negra, en el distrito de San Antonio de Cumbaza - San Martin - Vásquez Bartra, Fernando (2000)
With the aim to find the best moment for pruning and determinate its inf1uence upon the yield on grapevine of the variety Black Burgundy, (Vitis labrusca) this thesis was made between the month of January and July 1999 in the District of San Antonio de Cumbaza, in the Province and Department of San Martín, situated at latitude South 06025', and longitude West 76025' and a height of 800 m above sea level. The experimental design used was the block completely al random (DBCA) wilh four repetitions and six treatments plus one proof. The experiment was carried out in a approximately 5-6 years old vineyard. We studied the rest days after harvesting until pruning on grapevine in the following way: T1 (pruning after 10 days). T2 (pruning after 15 days). T3 (pruning after 20 days - proof), T4 (pruning after 25 days), T5 (pruning after 30 days), TG (pruning after 35 days) and T7 (pruning after 40 days), without considering the number of plants inside the experimental field; carrying out altogether 28 treatments or experimental units. In all the treatments we studied we applied a growth control called hydrogenated cyan amide (DORMEX) with a 3% concentration, in order to uniformize and activize the coming up of the buds after pruning. On the other hand, we carried ou1 six applications, two preventive (after 12 and 29 days) and four curative (after 38, 54, 70 and 85 days) applications, in order to control fungous diseases during the development of the grapevine, after the pruning on the whole vine arbor, using the chemical product Metalaxil + Mancozeb (Ranchapaj) in a dosis of 50g / 151trs water, mixing it with adhesion (Agridex) in a dosis of 10ml I 20Jtrs water. These applications succeeded to control the existence of Mildiu (plasmopors viticola), a very frequent disease in the grapevine cultivation in our region. The parameters of evaluation were: days of budding, number of buds per shoot, number of bunches per bud, number of filled up grains per treatment, number of ripe grains at harvest per trea1ment, number of bunches per treatment, grape yield per treatment (Kg), size of the bunch (cm),. With the obtained results we carried out the economic analysis relating the costs - profit in each treatment. The best results in the study of the influence of the moment of pruning grapevine on the yield have been reached with the treatment T7 (pruning at 40 days after harvesting) with a yield of fresh grapes of 3950,47 Kg per Ha., with a net profit of 2232.05 US$ per Ha.